The Economic and Social Environment of Irbid City - Talafha, Nehal; Khawaldah, Hamzah (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to reveal the socio-economic characteristics of the population in different neighborhoods in the city of Irbid. In addition, it seeks to demonstrate the variations among the city’s neighborhoods based on their demographic characteristics and housing attributes, while identifying the factors that contributed to these variations. Methods: The study employed the analytical approach using exploratory factor analysis to investigate the relationship between socio-economic and demographic factors, and the distribution of these factors across the city was examined using data from the General Population and Housing Census for the year 2015. A total of 37 variables were analyzed across 41 residential neighborhoods. The variables were transformed into percentages, forming an information matrix which was then inputted into statistical software, specifically the Statistical Package for the Social Sciences (SPSS), to conduct factor analysis. Results: The study identified four factors that explained the internal structure of the city of Irbid. The first factor is the economic and social factor, which accounts for (41.084%) of the total variance. The housing characteristics factor accounts for (21.372%), and the factor of nationality and housing ownership accounts for (13.120%) of the total variance. Finally, the characteristics of the head of the family factor explained (7.120%) of the total variation. Collectively, these factors explained (82.696%) of the total variance of the variables, which means that (82.696%) of the information included in the variables included in the study could be explained by the factors derived by factor analysis. Conclusions: The findings of the current study align with results from similar studies conducted in other Jordanian and Arab cities but diverge from those of Western cities. The study recommends that future urban planning endeavors consider the socioeconomic disparities, housing attributes, and ownership patterns when contemplating city expansion directions, as these factors significantly impact the city’s internal structure.